PERBANDINGAN BANYAK KATEGORI RESPON TERHADAP RELIABILITAS INSTRUMEN DISPOSISI MATEMATIKA - SITI MUSLIHAH HADI (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2013)
This study aimed to look at the comparation of number response categories towards reliability of mathematics disposition instrument. The research method used in this study is an experimental method. While the design used is one way anava of 4 x 1 and research hypotheses were tested using one way analysis of variance (ANOVA). The participants of this study were 765 students from eleventh grade in 4 SMAN in Central Jakarta with sampling technique multi stage random sampling. The result concluded that: (1) there is an influence of number response categories towards reliability coefficient of mathematics disposition instruments, (2) reliability of seven categories response mathematics disposition instrument higher than reliability of five categories response mathematics disposition instrument, (3) reliability of seven categories response mathematics disposition instrument higher than reliability of four categories response mathematics disposition instrument , and (4) reliability of six categories response mathematics disposition instrument higher than reliability of four categories response mathematics disposition instrument. Implementation of the study about adding two or three categories on non test instrument can be implemented for mathematics subject for student of Senior High School because of reliability enhancement.